Dignitas connubii e i matrimoni di non cattolici. Una conquista da conservare, migliorare ed estendere (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Introduzione - 2. Norme di conflitto del diritto canonico - 3. Visione d’insieme delle disposizioni - 3.1. Competenza dei tribunali ecclesiastici - 3.2. Il diritto processuale applicabile - 3.3. Il diritto sostanziale applicabile - 3.4. Il valore del diritto divino - 4. Dignitas connubii e Mitis iudex - 4.1. La Dignitas connubii è ancora in vigore? - 4.2. Processus brevior per matrimoni di non cattolici? - 5. L'art. 4 DC nella prassi giudiziale - 5.1. Una sentenza a Vancouver - 5.2. Aspetti processuali - 5.3. Il diritto sostanziale da applicare - 5.4. Terminologia - 6. Argomenti non presenti nella Dignitas connubii - 6.1. Riconoscimento di sentenze di nullità matrimoniale straniere - 6.2. Vizio di forma accertabile nell'esame degli sposi - 6.3. Quale tribunale cattolico è competente? - 7. Uno sguardo a possibili sviluppi futuri.Dignitas connubii and marriages of Non-Catholics. An achievement to be maintained, improved and complementedAbstract: The instruction Dignitas connubii of 2005, Art 2-4, deals with marriages, in which one or both parts are non-Catholic - whether baptized or not. This is a great progress initiated by the Second Vatican Council, even if there still are some omissions and ambiguities in the regulations. Since 2005, some jurisprudential experience could be gained and further official documents concerning non-Catholic marriages have been issued. They are mainly dealing with Orthodox Christians and are dedicated to the recognition of matrimonial sentences, the determination of formal defects and competence issues. Mitis iudex does not mention anything concerning this topic but in case a new instruction should be made now, the named Articles would have to be maintained, improved and complemented.